2015
DOI: 10.1152/ajpheart.00825.2014
|View full text |Cite
|
Sign up to set email alerts
|

Small-conductance Ca2+-activated K+ current is upregulated via the phosphorylation of CaMKII in cardiac hypertrophy from spontaneously hypertensive rats

Abstract: Left ventricular hypertrophy is associated with an increased risk of ventricular arrhythmias. However, the underlying molecular basis is poorly understood. It has been reported that small-conductance Ca(2+)-activated K(+) (SK) channels are involved in the pathogenesis of ventricular arrhythmias in heart failure. The present study aimed to test the hypothesis that SK channel activity is increased via the Ca(2+)/calmodulin-dependent protein kinase II (CaMKII)-dependent pathway in hypertensive cardiac hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…CaMKII activity is enhanced in clinical and experimental models of AF [ 15 17 ]. SK channels are upregulated via the enhanced activation of CaMKII in hypertrophic hearts of spontaneously hypertensive rats [ 18 ]. Therefore, we hypothesized that increased CaMKII activity enhances the intracellular calcium sensitivity of SK channels in human chronic AF, and the present study was designed to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…CaMKII activity is enhanced in clinical and experimental models of AF [ 15 17 ]. SK channels are upregulated via the enhanced activation of CaMKII in hypertrophic hearts of spontaneously hypertensive rats [ 18 ]. Therefore, we hypothesized that increased CaMKII activity enhances the intracellular calcium sensitivity of SK channels in human chronic AF, and the present study was designed to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in failing and hypertrophied hearts, these channels played an important role in the ventricular repolarization (Chua et al, 2011;Mizukami et al, 2015). We also reported that SK channels were upregulated via Kamada et al,Page 5 activation of CaMKII in hypertrophied rat hearts (Mitsuyama et al, 2014;Mizukami et al, 2015). At present, it is not well known that activation of SK channels produces antiarrhythmic or proarrhythmic functions (Chang et al, 2013;Chua et al, 2011).…”
Section: Introductionmentioning
confidence: 70%
“…It was reported that SK channels had a little contribution to the ventricular repolarization during action potentials of normal hearts (Nagy et al, 2009) . In contrast, in failing and hypertrophied hearts, these channels played an important role in the ventricular repolarization (Chua et al, 2011;Mizukami et al, 2015). We also reported that SK channels were upregulated via Kamada et al,Page 5 activation of CaMKII in hypertrophied rat hearts (Mitsuyama et al, 2014;Mizukami et al, 2015).…”
Section: Introductionmentioning
confidence: 72%
“…Although there was an increase in total MAPK/ErK in PVN total lysate (Figure 6b ; p < 0.05), confocal imaging revealed a decrease in MAPK/ErK—specifically—for eGFP positive PVN neurons in TLR4 Cre/− ISOP group (Figure 6a ; p < 0.01). Since it has been established that p-MAPK/ErK phosphorylates CaMKIIα (Mizukami et al, 2015 ; Yu et al, 2016 ), we further quantified the expression of PVN p-MAPK/ErK in the PVN. Although TLR4 Cre /− ISOP group recorded a higher PVN MAPK/ErK expression, there was a significant decrease in p-MAPK/ErK when compared with the TLR4 loxp / loxp ISOP group ( p < 0.001) after ISOP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Through its effect on TLR4 and NMDAR, βAR affects nNOS, and GABA neurotransmission in the brain; further increasing excitatory glutamatergic potentials (Sharma et al, 2011 ; Lethbridge et al, 2012 ; Di Mauro et al, 2013 ). Similarly, TLR4-mediated MAPK/ErK activation leads to inflammation via phosphorylation of calcium-calmodulin dependent kinase II alpha (CaMKIIα) (Mizukami et al, 2015 ; Yu et al, 2016 ). Thus, we hypothesize that attenuating MAPK/ErK inflammatory signaling events, in the PVN neurons, may reduce the severity of sympathoexcitation by reducing the phosphorylation of CaMKIIα.…”
Section: Introductionmentioning
confidence: 99%